Cognitive impairment in intensive care unit patients: A pilot mixed-methods feasibility study exploring incidence and experiences for recovering patients. Issue 2 (March 2019) - Elliott, Rosalind; Yarad, Elizabeth; Webb, Sarah; Cheung, Katherine; Bass, Frances; Hammond, Naomi; Elliott, Doug
Abstract: Background: Despite improvements in survival after critical illness and intensive care unit (ICU) treatment, some recovering patients still face ongoing challenges. There are few investigations exploring the incidence, risk factors, and trajectory for cognitive impairment (CI) in former ICU patients in Australia. Objectives: To test the feasibility of a study protocol designed to ascertain the incidence and impact of CI during recovery from a critical illness. Methods: We conducted a mixed-methods longitudinal single-centre pilot study. Participants were adult patients mechanically ventilated for ≥48 h. Cognitive function was assessed during hospitalisation and at 1 week, 2 months, and 6 months after hospital discharge, using the Montreal Cognitive Assessment instrument. Factors potentially affecting cognitive function were also collected, including demographic and clinical variables and fatigue, frailty, and muscle strength. Semistructured interviews were conducted to further explore participants' experiences during recovery. Results: We screened 2068 patients (10% met the inclusion criteria). Participants (n = 20) were mostly male with a mean age 61.9 years and a median of 4 days of mechanical ventilation. Data collection was complete for 14 and 11 participants at 2 months and 6 months, respectively. Pre-illness patients were not cognitively impaired; one patient had delirium in ICU. The proportion of patients with CI ranged from 80% (17/18) while in hospital to 35% (5/14) at 6 months. Participants were challenged by fatigue and sleep disruption during recovery but were not particularly concerned about CI. Conclusions: Recruitment in ICU was challenging as few patients received prolonged mechanical ventilation. The protocol was feasible, but some attrition was noted. A significant proportion of patients had mild CI, largely confined to recall, and language cognitive domains; quantitative findings were supported by interview findings. Further investigations are required to ascertain the most appropriate inclusion criteria to enable identification of those at highest risk of CI.